Benefits and limitations of using innovative tools like detection dogs, thermal imaging and drones to increase wildlife carcass finds during health surveillance and management efforts - Sandor, Camille; Desvaux, Stéphanie; Palumbo, Loïc; Larrat, Sylvain; Charabidze, Damien; D’artois, Patrick; Decors, Anouk (Frontiers in Conservation Science, 2025)
Recent awareness of the role of wildlife in the evolution of emerging zoonotic diseases emphasizes the needs to conduct surveillance for public health. Additionally, wildlife surveillance is motivated by animal health, conservation and biodiversity perspectives. Event-based wildlife surveillance involves studying mortality and investigating its causes. Carcass detection thus plays a key role in the surveillance of high-risk diseases. Many factors influence the degradation of a carcass, particularly environmental conditions, the biology and behavior of the species, and the role played by necrophagous insects and scavengers. Various tools and technologies have been tested over the years to improve wildlife carcass detection. Here, we review the main factors that influence carcass detectability and detection in wildlife surveillance and management, alongside the strengths and limitations of key innovative detection tools: detection dogs, drones and thermal imaging. We also list decision criteria to help wildlife surveillance managers and researchers understand and select the targeted search approaches most likely to optimize carcass encounter and recovery during disease outbreaks.